Analysis of the effect of cutting depth under thick immediate roof on gob-side entry retaining stability - WANG Fei; WANG Xuqiang; SHI Xinyu; XU Huicong (Gong-kuang zidonghua)
The stability of gob-side entry retaining with roof cutting and pressure relief is primarily influenced by roof cutting parameters. However, determining appropriate cutting parameters for gob-side entry under the effect of a thick immediate roof is relatively complex. Taking the auxiliary transport roadway of the 1009 working face at No. 1 Coal Mine of Shaanxi Shanmei Huangling Mining Industry Co., Ltd. as the engineering background, a combination of theoretical analysis, numerical calculation, and field monitoring was employed in this study. Based on the understanding that the gob-side entry retaining process includes "reinforcement support, roof cutting and pressure relief, sidewall support, and temporary support within the roadway", the study analyzed the process and appropriate parameters of gob-side entry retaining under the effect of a thick immediate roof. It examined the mining pressure manifestation patterns, as well as the roadway stress and displacement characteristics under roof cutting depths of 7.5, 8.5, and 9.5 m, determining the reasonable roof cutting depth for the gob-side entry. Field monitoring was conducted to verify the effectiveness of the entry construction outcome. The results indicated that the cutting depth directly affected the entry construction outcome. When the cutting angle was fixed, the closer the cutting depth was to the thickness of the immediate roof, the greater the support force from the caving gangue to the roof, resulting in stronger stability of the rock strata. As the cutting depth increased, the step distance of the mining pressure decreased, the pressure intensity reduced, and the peak value of the stress concentration and roof subsidence displacement in the roadway reduced. The optimal cutting depth was determined to be 8.5 m, at which point the peak stress concentration and maximum displacement of the roadway after completion were 13.6 MPa and 235 mm, respectively. Field monitoring results showed that after entering the stable gob-side entry retaining section, the maximum subsidence of the roadway was 252 mm, the maximum load of the pressure-relief anchor cable was 412 kN, and the maximum working resistance of the stacking support was 41.9 MPa. The roadway stability was excellent, and the gob-side entry retaining effect was significant.